Molecular profiling of pediatric mature B-cell lymphoma treated in population-based prospective clinical trials - Klapper, Wolfram; Szczepanowski, Monika; Burkhardt, Birgit; Berger, Hilmar; Rosolowski, Maciej; Bentink, Stefan; Schwaenen, Carsten; Wessendorf, Swen; Spang, Rainer; Möller, Peter; Hansmann, Martin Leo; Bernd, Heinz-Wolfram; et al. (Blood, 2008)
The spectrum of entities, the therapeutic strategy, and the outcome of mature aggressive B-cell non-Hodgkin lymphomas (maB-NHLs) differs between children and adolescents on the one hand and adult patients on the other. Whereas adult maB-NHLs have been studied in detail, data on molecular profiling of pediatric maB-NHLs are hitherto lacking. We analyzed 65 cases of maB-NHL from patients up to 18 years of age by gene expression profiling, matrix comparative genomic hybridization (CGH), fluorescent in situ hybridization (FISH), and immunohistochemistry. The majority of the analyzed pediatric patients were treated within prospective trials (n = 49). We compared this group to a series of 182 previously published cases of adult maB-NHL. Gene expression profiling reclassified 31% of morphologically defined diffuse large B-cell lymphomas as molecular Burkitt lymphoma (mBL). The subgroups obtained by molecular reclassification did not show any difference in outcome in children treated with the NHL-Berlin-Frankfurt-Muenster (BFM) protocols. No differences were detectable between pediatric and adult mBL with regard to gene expression or chromosomal imbalances. This is the first report on molecular profiling of pediatric B-NHL showing mBL to be much more prominent in children than suggested by morphologic assessment. Based on molecular profiling mBL is a molecularly homogeneous disease across children and adults.